Phytochemical screening and GC-MS analysis of Mukia maderaspatana (L.) leaves - G. Gomathya , b, T.Vijayc, K.Sarumathyd, S.Gunasekarane, S.Palanif (Journal of Applied Pharmaceutical Science)
The investigation was carried out to determine the qualitative analysis of phytochemical screening and possible chemical components of Mukia maderaspatana (L.) (family: Cucurbitaceae), leaves GC-MS. The plant is an indigenous plant; traditionally it is used as an ingredient of various cocktail preparations and for the management of severe inflammatory disorders in Indian system of medicine. GC-MS analysis of hydroalcoholic extract lead to identification of 7 compounds. This analysis revealed that contains Mukia maderaspatana (L.) leaves mainly Dichloroacetic acid, 4-methylpentyl ester, 2-Butyn-1-ol, 4-methoxy and also showed the presence of other constituents like flavonoids, saponins, carbohydrates, steroids, tannins and phenolic compounds.
Keywords: Mukia maderaspatana (L.), GC-MS analysis, Dichloroacetic acid, 4-methylpentyl ester, 2-Butyn-1-ol, 4-methoxy.